Fluorescence and phosphorescence - Rendell, David (New Delhi Wiley India, 1987)
This introduction to a major area of growth in analytical chemistry is designed for students seeking general background on the subject and for established chemists who want greater familiarity with the uses of fluorescence and phosphorescence techniques. The complicated aspects of spectroscopic theory is treated clearly and simply, providing a solid basis for understanding the analytical applications described later in the book. It outlines the instrumentation required in analysis, with block diagrams to clarify major concepts and explains the quantitative aspects of photoluminescence. The remainder of the book surveys methods of both organic and inorganic analytes using natural flourescence or the formation of fluorescent derivatives. It includes coverage of recent developments such as flour immunoassay and room temperature phosphorescence. Case studies give concrete examples of current work in the field
Keywords: PHARMACEUTICAL ANALYSIS